EL JUSTURISMO - Armas Morales, Carlos (2004)
Tourism, as a social phenomenon, has led to the birth of a new industry and the so called "Tourism Laui" ar "[usiurismo", as proposed by the author. It refersto the assembly of principies, rules and precepts to which are subject all institutions and relationships grown out of tourism. This article analyses ihe legal opinion as an independent discipline within the legal arder.